Chemical and Noble Gas Isotope Compositions of Formation Gases from a 3 km Deep Scientific Borehole in the Koyna Seismogenic Zone, Western India - Nagaraju Podugu; Satrughna Mishra; Thomas Wiersberg; Sukanta Roy (Geofluids)
A 3 km deep research borehole KFD1 was drilled in the Koyna reservoir-triggered seismicity region, Western India, between December 2016 and May 2017. The 1967 M 6.3 Koyna earthquake had generated a NNE-SSW trending surface fissure zone in the Nanel-Donichawadi-Kadoli sector. KFD1 is located ~5 km south of Kadoli along the trend of the Donichawadi fault zone. Online gas monitoring was carried out during drilling of KFD1 from 1315 m to 2831 m depth to sample and study the composition of crustal gases. Formation gases CO2, CH4, H2, and He were only observed during water flushing of ~100 m intervals following coring runs. Laboratory analyses of gas samples collected between 1737 m and 2831 m depth revealed concentrations of up to 1200 ppmv CO2, 186 ppmv CH4, 139 ppmv H2, and 12.8 ppmv He. Zones enriched in gases are mostly below the 2100 m depth with significant He enhancement ranging from 4.6 to 7.6 ppmv above the atmospheric value. The He-rich zones correlate well with the zones of anomalous physical and mechanical properties identified from geophysical logs and are characterized by high fracture density as revealed from borehole images, indicating that the borehole punctured multiple fracture zones. The helium concentrations are consistent with those previously observed over the surface fissures near Kadoli, suggesting a southward extension of the Donichawadi fault zone up to the KFD1 site and confirming that the fault zone is permeable even after 50 years of the 1967 Koyna earthquake. 3He/4He ratios of eleven gas samples fall between 0.426±0.022 and 0.912±0.059 Ra, with 4He/20Ne values between 0.3449±0.0091 and 0.751±0.020. Air-corrected helium isotope ratios indicate that helium is a mixture of atmospheric and crustal radiogenic components but no mantle contribution within 2σ analytical uncertainties.